B-Mode Transorbital Ultrasonography for the Diagnosis of Idiopathic Intracranial Hypertension: A Systematic Review and Meta-Analysis - Lochner, Piergiorgio; Fassbender, Klaus; Knodel, Sophia; Andrejewski, Anika; Lesmeister, Martin; Wagenpfeil, Gudrun; Nardone, Raffaele; Brigo, Francesco (Ultraschall in der Medizin - European Journal of Ultrasound, 2019)
In patients with idiopathic intracranial hypertension (IIH), transorbital sonography (TOS) may reveal an enlargement of the optic nerve sheath diameter (ONSD) and the presence of optic disc elevation (ODE), as a sign of an increase in intracranial pressure (ICP). We systematically reviewed the TOS findings in adults with IIH. MEDLINE, EMBASE, Cochrane Library and CENTRAL (1966 – May 2017) were searched to identify studies reporting data on patients with IIH assessed by B mode-TOS. Data were extracted and included in a meta-analysis, and the quality of the included studies was evaluated. 5 studies with 96 patients were included. The values of ODE were 0.8 – 1.2 mm and ONSD was 6.2 – 6.76 mm in IIH patients vs. 4.3 – 5.7 mm in controls. In IIH patients the ONSD was significantly higher compared to controls (overall weighted mean difference of 1.3 mm (95 % CI: 0.6 – 1.9 mm)). The meta-analysis of proportion of papilledema based on results of three studies revealed a pooled estimator of 87 % (95 % CI: 76 – 94 %). IIH patients have higher ONSD values and higher frequency of ODE compared to controls. The indirect, noninvasive ICP assessment using TOS may be useful in supporting the clinical diagnosis of IIH in adults by detecting increased ONSD values and the presence of ODE.
Keywords: idiopathic intracranial hypertension; intracranial pressure; optic disc elevation; optic nerve sheath diameter; transorbital sonography